Induction of phloem unloading in Arabidopsis thaliana roots by the parasitic nematode Heterodera schachtii. - Böckenhoff, A (1996)
Phloem unloading of both the fluorescent probe carboxyfluorescein (CF) and 14C-labeled solutes was induced in Arabidopsis thaliana L. roots by the parasitic nematode Heterodera schachtii Schmidt. Confocal laser scanning microscopy demonstrated that anomalous unloading of CF from the sieve element companion cell complexes occurred specifically into the syncytium, the nematode-induced feeding structure located within the stele of the root. From this syncytial complex of modified root cells, both fluorescent and radioactive labels were withdrawn by feeding nematodes. Movement of CF was unidirectional from the phloem to the syncytium. A range of low-molecular-weight fluorescent probes (including CF) microinjected into the syncytium stayed in this structure, demonstrating that it is symplastically isolated from the surrounding root tissue. The mechanism of unloading in this host-pathogen relationship therefore appears to be apoplastic. Our results provide unequivocal evidence that sedentary cyst-forming nematodes have direct access to phloem-derived solutes.